2020
DOI: 10.3390/ijms21249709
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Product Inhibitor Pyridoxamine Attenuates IVD Degeneration in Type 2 Diabetic Rats

Abstract: Type 2 diabetes mellitus (T2DM) is associated with advanced glycation end product (AGE) enrichment and considered a risk factor for intervertebral disc (IVD) degeneration. We hypothesized that systemic AGE inhibition, achieved using pyridoxamine (PM), attenuates IVD degeneration in T2DM rats. To induce IVD degeneration, lumbar disc injury or sham surgery was performed on Zucker Diabetic Sprague Dawley (ZDSD) or control Sprague Dawley (SD) rats. Post-surgery, IVD-injured ZDSD rats received daily PM dissolved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…Histological analysis of injected IVDs (L4/5, L5/L6 levels) of all tested groups showed no visible disc degeneration compared to reported degeneration models ( 47, 64, 65 ) 8 weeks post intradiscal injection (Fig. 6E).…”
Section: Resultsmentioning
confidence: 87%
“…Histological analysis of injected IVDs (L4/5, L5/L6 levels) of all tested groups showed no visible disc degeneration compared to reported degeneration models ( 47, 64, 65 ) 8 weeks post intradiscal injection (Fig. 6E).…”
Section: Resultsmentioning
confidence: 87%
“…Histological analysis of IVDs (L4/5 and L5/L6 levels) at 8 weeks after intradiscal injection showed no visible disc degeneration ( 47 , 75 , 76 ) in any of the treatment groups (Fig. 5E).…”
Section: Resultsmentioning
confidence: 96%
“…MRI image analysis showed that oral treatment with the AGE inhibitor PM could reduce NP dehydration after needle injury. PM also promoted the increase in the level of oligosaccharides in rats ( 75 ). In addition, AGEs-BSA can induce mitochondrial damage in NP cells through activation of NLRP3 inflammatory bodies, resulting in a secondary inflammatory response ( 76 ).…”
Section: Abnormal Glucose Metabolism and Iddmentioning
confidence: 95%